The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2147/ndt.s159562
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of night-eating syndrome occurrence in women in Poland, considering the obesity factor in particular

Abstract: IntroductionNight-eating syndrome (NES) involves uncontrolled and most often repeated binge eating during the night. It is related with mood disorders as well as sleep disorders and it may cause obesity. Risks related to NES are obesity, binge eating disorder, bulimia nervosa, affective disorders, and sleep disorders. The objective of this study is to analyze eating habits in terms of the risk assessment of NES occurrence in the population of women in the Masovian Voivodeship (in Poland).Patients and methodsSi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…A systematic review confirmed that eating disorders could have a noticeable impact on HRQoL, and patients with anorexia nervosa, bulimia nervosa, and binge eating disorder reported significantly worse scores than the healthy comparison groups [ 25 ]. Similarly, a previous study theorized that individuals with NES may have poorer quality of life since NES is known to increase the risk of many disorders, including affective disorders [ 10 , 26 ]. Since HRQoL encompasses a diverse spectrum of health-related functioning, poorer HRQoL scores may be found in individuals with NES as revealed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review confirmed that eating disorders could have a noticeable impact on HRQoL, and patients with anorexia nervosa, bulimia nervosa, and binge eating disorder reported significantly worse scores than the healthy comparison groups [ 25 ]. Similarly, a previous study theorized that individuals with NES may have poorer quality of life since NES is known to increase the risk of many disorders, including affective disorders [ 10 , 26 ]. Since HRQoL encompasses a diverse spectrum of health-related functioning, poorer HRQoL scores may be found in individuals with NES as revealed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The NEQ is a 14‐item questionnaire frequently used to assess behavioral and psychological symptoms of night eating. Responses were measured on a 5‐point Likert scale (0 = not at all, 4 = extremely) and a cutoff of 25 points was applied based on previous studies (Olejniczak et al, 2018; Sevincer, Ince, Taymur, & Konuk, 2016). Scores range from 0 to 52 points in the NEQ.…”
Section: Methodsmentioning
confidence: 99%
“…There exists sizeable evidence in the literature on the relationship between NES, anxiety, depression, and BMI (15). A recent prospective study revealed that no clear association exists between obesity and NES (16) although several clinical trials have linked NES directly to obesity (17,18). This disparity could be due to the variations in diagnostic criteria of NES and population characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers worldwide have identified certain factors believed to be affecting the academic performance of students. These could be categorized into academic, demographic, cognitive and psychosocial variables (18). A psychosocial variable of academic achievements could be the presence of NES among students.…”
Section: Introductionmentioning
confidence: 99%